the TRADISI MONGUBINGO DI DESA HUNGAYONAA KEC. TILAMUTA KAB. BOALEMO: (KAJIAN LIVING HADIS) - Sultani, Hikmawati; panigoro, muhammad Rifian; Agustina Saliko, Risvan (LPPM IAIN Sultan Amai Gorontalo, 2021)
One phenomena of living hadith in Gorontalo was Mongubingo tradition in Hungayonaa Village, Tilamuta District, and Boalemo Regency. The aim of the study was to explore the living hadith in Hungayonaa Village community. The method used was descriptive-analytic by using a philosophical historical approach. Method of collecting data used observation and interviews. The results indicated that Mongubingo tradition is believed to be teaching of the prophet which has been passed down from heritage to this day. People got that the order to carry out female circumcision is an obligation as an implication of obedience to customs based on Kitabullah and hadith. But their knowledge is only limited to the meaning on substance of the hadith and had no idea the existence of the hadith text which is used as a reference in religion. As for the ritual practice of Mongubingo or circumcision, it is adapted to the context of Gorontalo community, especially in the Hungayonaa Village, as a result of acculturation between tradition and Islam.